Strategies of Adaptation Capacity Improvement Among The Natural Disaster Victims - Suharyono, Sri; Suci Indraningsih, Kurnia (SOCA: Jurnal Sosial Ekonomi Pertanian, 2022)
The natural disaster eruption of Mount Merapi in 2010 had relocated several farming communities. Building a new life after a disaster in an unfamiliar environment posed a tough challenge and required an adaptation strategy. This study aimed to investigate the adaptive capacity possessed and its improvement strategy among Mount Merapi eruption victims. The current study was conducted in the permanent shelter of Kuwang and Randusari, Argomulyo Village, Cangkringan District, Sleman Regency, Yogyakarta. Qualitative descriptive method applied to analyze the data. Eighty study participants from different household were selected purposively. Findings revealed that the adaptive capacity of the institutional memory, innovative learning, and connectedness was in poor, poor, and good category, respectively. Community adaptation strategy included three aspects, namely: physical adaptation by house renovation, economic adaptation through job diversification, and social adaptation by social activities involveme